Ca. Similichlamydia in Epitheliocystis Co-infection of Gilthead Seabream Gills: Unique Morphological Features of a Deep Branching Chlamydial Family - Seth-Smith, Helena M. B.; Katharios, Pantelis; Dourala, Nancy; Mateos, José M.; Fehr, Alexander G. J.; Nufer, Lisbeth; Ruetten, Maja; Guevara Soto, Maricruz; Vaughan, Lloyd (Frontiers in Microbiology, 2017)
The Planctomycetes-Verrucomicrobia-Chlamydiae (PVC) bacterial superphylum constitutes a broad range of organisms with an intriguing array of ultrastructural morphologies, including intracellular membranes and compartments and their corresponding complex genomes encoding these forms. The phylum Chlamydiae are all obligate intracellular bacteria and although much is already known of their genomes from various families and how these regulate the various morphological forms, we know remarkably little about what is likely the deepest rooting clade of this phylum, which has only been found as pathogens of marine and fresh water vertebrates. The disease they are associated with is called epitheliocystis, however, analyses of the causative agents is hindered by an inability to cultivate them for refined in vitro experimentation. For this reason, we have developed tools to analyse both the genomes and the ultrastructures of bacteria causing this disease, directly from tissues. Here we present structural data for a member of the family Ca. Similichlamydiaceae from this deep-rooted clade, which we have identified using molecular tools in epitheliocystis lesions of gilthead seabream (Sparus aurata) in Greece. We present evidence that the chlamydial inclusions appear to develop in a perinuclear location, similar to other members of the phylum and that a chlamydial developmental cycle is present, with chlamydial forms similar to replicating bodies (RBs) and elementary bodies (EBs) detected. Division of the RBs appeared to follow a budding process and larger RBs with multiple condensed nucleoids were detected using both transmission electron microscopy (TEM) and by focused-ion beam, scanning electron microscopy (FIB-SEM). As model hosts, fish offer many advantages for investigation, and we hope by these efforts to encourage others to explore the biology of fish pathogens from the PVC.